Elucidation of pineapple softening based on cell wall polysaccharides degradation during storage - Li, Fengjun; Xia, Xingzhou; Li, Lilang; Song, Longlong; Ye, Yuping; Jiang, Yueming; Liu, Hai (Frontiers in Plant Science, 2024)
Experiments were conducted to investigate tThe degradation of cell wall polysaccharides in pineapple fruit during softening was investigated in the present study. Two pectin fractions and two hemicellulose fractions were extracted from the cell wall materials of 'Comte de Paris' pineapple fruit at five softening stages, and their compositional changes were subsequently analyzed. The process of softening of the fruit corresponded to an increase in the water-soluble pectin (WSP) and 1 M KOHsoluble hemicellulose (HC1) fractions, and a decrease in the acid-soluble pectin (ASP) fraction, which suggested the solubilization and conversion of cellular wall components. However, the content of 4 M KOH-soluble hemicellulose (HC2) decreased and then returned to the initial level. Furthermore, WSP, ASP, and HC1 showed an increment in the content of low molecular weight polymers while a decline in the high molecular weight polymers throughout softening, and not significant change in the contents of different molecular polymers of HC2 was observed. Moreover, the galacturonic acid (GalA) content in the main chain of WSP was maintained at a relatively constant levelbasically, but the major branch monosaccharide galactose (Gal) in WSP decreased. Different from WSP, the molar percentages of Gal and GalA in ASP decreased. The Gal or Arabinose (Ara) in HC1 exhibited a gradual declinetended to decrease gradually while the molar percentages of xylose (Xyl) and glucose (Glu) in the main chain increased. These suggested that the main chain of ASP degraded while the branched chains of ASP, WSP and HC1 depolymerized during pineapple softening. Overall, fruit softening of 'Comte de Paris' pineapple was found to be the result ofinvolved in differential modification of pectin and hemicellulose.